2019
DOI: 10.1177/1055665619829388
|View full text |Cite
|
Sign up to set email alerts
|

Cleft Palate Outcomes and Prognostic Impact of Palatal Fistula on Subsequent Velopharyngeal Function—A Retrospective Cohort Study

Abstract: Objective: To assess outcomes from cleft palate repair and define the level of impact of palatal fistula on subsequent velopharyngeal function. Design: A retrospective cohort study. Setting: A regional specialist cleft lip and palate center within United Kingdom. Patients, Participants: Nonsyndromic infants born between 2002 and 2009 undergoing cleft palate primary surgery by a single surgeon with audited outcomes at 5 years of age. Four hundred ten infants underwent cleft palate surgery within this period and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 15 publications
3
12
0
Order By: Relevance
“…In contrast, Becker & Hansson (2013) concluded that their low fistula rate (5%) after using the Sommerlad technique was due to their liberal use of lateral releasing incisions (42% of their cohort), considerably higher than in this study. Our study found the highest prevalence of fistula in PRS, in line with others (Lu et al, 2010, Moar et al, 2016, Smyth & Wu, 2019). Furthermore, Lu et al (2010) reported that their fistula rate decreased significantly with greater number of years of surgeon experience, as has also been reported here.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, Becker & Hansson (2013) concluded that their low fistula rate (5%) after using the Sommerlad technique was due to their liberal use of lateral releasing incisions (42% of their cohort), considerably higher than in this study. Our study found the highest prevalence of fistula in PRS, in line with others (Lu et al, 2010, Moar et al, 2016, Smyth & Wu, 2019). Furthermore, Lu et al (2010) reported that their fistula rate decreased significantly with greater number of years of surgeon experience, as has also been reported here.…”
Section: Discussionsupporting
confidence: 93%
“…Others have published on the Sommerlad soft palate repair technique (Andrades et al, 2008; Becker & Hansson, 2013; Doucet et al, 2013; Luyten et al, 2013; 2014; Yang et al, 2013; Cairns et al, 2014; Moar et al, 2016; Rossell-Perry et al, 2015; Dissaux et al, 2016; Nyberg et al, 2018; Bruneel et al, 2018; Klinto et al, 2018; Mapar et al, 2019; Smyth & Wu, 2019). In 3 studies, the Sommerlad intravelar veloplasty was part of a protocol of delayed hard palate closure (Doucet et al, 2013; Dissaux et al, 2016; Klinto et al, 2018 [in 2 of 3 centers]); in another 2 studies, gold standard speech methodology was not used (Andrades et al, 2008; Yang et al, 2013); in 3 studies detailed speech results were not given (Becker & Hansson, 2013; Rossell-Perry et al, 2015; Moar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Our study supports the finding that palatal fistulae increase the likelihood of VPI postoperatively (Smyth & Wu, 2019). This is unsurprising, as fistulae inherently cause defects in the velopharyngeal seal, leading to hypernasality and regurgitation.…”
Section: Discussionsupporting
confidence: 92%
“…By identifying factors associated with the development of VPI, cleft teams may be able to counsel patients and tailor surgical treatment plans in advance of the primary repair to mitigate increased risks for the development of VPI. Numerous studies have examined patient factors associated with the development of VPI, suggesting a multifactorial nature involving genetic, anatomic, and surgical factors (Cohen et al, 1991; Randall et al, 2000; Sweeney et al, 2015; Yuan et al, 2016; Smyth & Wu, 2019; Stein et al, 2019). However, further studies are needed to determine the exact roles of these factors in the development of VPI (Sainsbury et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…29,30 This rate more than doubles for cleft palate patients that develop a palatal fistula. 30 Indeed, the majority of patients in our sample had a diagnosis of cleft lip and/ or palate. Cleft patients may be at increased risk of obstructive sleep apnea because of abnormal dimensions of the maxilla and mandible, a small nasopharyngeal space, and scarring from prior procedures.…”
Section: Discussionmentioning
confidence: 99%